An Evaluation of Information Meetings as a Tool for Addressing Fear of Large Carnivores. Issue 3 (4th March 2017) - Johansson, Maria; Frank, Jens; Støen, Ole-Gunnar; Flykt, Anders
ABSTRACT: Managing authorities in Scandinavia arrange public information meetings when members of the public express fear because wolves or brown bears approach human settlements. This study aimed to increase the understanding of the potential effect of information meetings on self-reported fear of wolves and brown bears. In total, 198 participants completed questionnaires before and after the information meetings. Nine follow-up interviews were held 1 year later. The quantitative analyses revealed that participants who found the information credible reported a significant increase in social trust and a decrease in vulnerability and fear. The qualitative analyses pointed to the importance of information content and meta-communication, for example, nonverbal cues. It is proposed that, among participants who find the information credible, information meetings may change the appraisal of wolves and brown bears, and therefore they might prove useful as an intervention to address fear of these animals.